MEMBANGUN WEBSERVER INTRANET DENGAN LINUX (Studi Kasus di Laboratorium Komputer SMP Negeri 38 Seluma Bengkulu Selatan) - Khairil, Khairil; Riyanto, Nugroho Ponco; Rosmeri, Rosmeri (UNIVED Press, 2013)
Build an intranet Web server is a method or action to solve the problems faced by schools are not reached by the internet. In this study the authors used Linux since using linux Authors can specify the criteria and weights are in want to build an Intranet Web Server in SMP N 38 Seluma. In building an Intranet Web Server researchers using PHP programming language and MySQL database are integrated in the package XAMPP 1.6.4 for Linux as well as the integration of technology LTSP (Linux Terminal Service Project) and Linux-based operating system Ubuntu 10.10 servers authors can easily build a web server in the intranet .